ChemInform Abstract: Intramolecular Carbolithiation of Heterosubstituted Alkynes: An Experimental and Theoretical Study. Issue 40 (October 2015) - Lhermet, Rudy; Ahmad, Maha; Hauduc, Clemence; Fressigne, Catherine; Durandetti, Muriel; Maddaluno, Jacques
Abstract Lithiation of 2‐iodophenyl‐propargylethers (I) results in a 5‐exo‐dig cyclization to yield products (II) selectively.